Recent structural studies of RNA polymerases II and III. (25th October 2006) - Cramer, P.
Abstract : Here, I review three new structural studies from our laboratory. First, the crystal structure of RNA polymerase (Pol) II in complex with an RNA inhibitor revealed that this RNA blocks transcription initiation by preventing DNA loading into the active-centre cleft. Secondly, the structure of the SRI (Set2 Rpb1-interacting) domain of the histone methyltransferase Set2 revealed a novel fold for specific interaction with the doubly phosphorylated CTD (C-terminal repeat domain) of Pol II. Finally, we obtained the first structural information on Pol III, in the form of an 11-subunit model obtained by combining a homology model of the nine-subunit core enzyme with a new X-ray structure of the subcomplex C17/25.